Thin Man - Hammett, Dashiell (New York : Vintage Books, 1992)
Nick and Nora Charles are Dashiell Hammett's most enchanting creations, a rich, glamorous couple who solve homicides in between wisecracks and martinis. At once knowing and unabashedly romantic, "The Thin Man" is a murder mystery that doubles as a sophisticated comedy of manners.
A Nick and Nora Charles mystery.
Keywords: Charles, Nick (Fictitious character); Charles, Nora (Fictitious character); Private investigators -- New York (State) -- New York; Women detectives -- New York (State) -- New York; Married people; New York (N.Y.); Mystery fiction